KUALITAS PELAYANAN PUBLIK KANTOR KECAMATAN MEKARSARI KABUPATEN BARITO KUALA BERDASARKAN INDEKS KEPUASAN MASYARAKAT (IKM) - Bakhtiar Bakhtiar; Rizalul Gadi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
The results of the study showed that the results of the community satisfaction survey on public service types of population administration in Mekarsari District Barito Kuala Regency based on the Community Satisfaction Index Value (IKM) was 77.25 which was included in the